Disopyramide is a safe and effective treatment for children with obstructive hypertrophic cardiomyopathy. (15th January 2023) - Topriceanu, Constantin-Cristian; Field, Ella; Boleti, Olga; Cervi, Elena; Kaski, Juan Pablo; Norrish, Gabrielle
Abstract: Background: Left ventricular outflow tract obstruction (LVOTO) is present in 1/3 of children with Hypertrophic Cardiomyopathy (HCM). Disopyramide improves symptoms associated with LVOTO and delays surgical intervention in adults, but it is not licensed in children. Aim: To describe a single-centre thirty-year experience of using disopyramide to treat LVOTO-related symptoms in a paediatric HCM cohort. Methods: Clinical data were collected for all patients meeting diagnostic criteria for HCM (<18 years) at the time of initiation, 6 months after, and last follow-up or end of disopyramide treatment. It included demographics, clinical history, 12‑lead electrocardiography, and echocardiography. Comparisons between baseline and 6 month follow up, and end of follow up respectively were performed. Results: Fifty-one patients with HCM were started on disopyramide at a mean age 10.2±5.3 years. At 6 months, of those previously symptomatic, 33(86.8%) reported an improvement of symptoms and 12(31.6%) were asymptomatic. PR interval, corrected QT interval and maximal LVOT gradient had not significantly changed, but fewer participants were noted to have systolic anterior motion of the mitral valve 31 (72.1%) vs. 26 (57.80%). Patients were followed up for a median of 1.9 years (IQR 0.83–4.5). Nine patients (17.6%) reported side effects, and eleven patients (33.3%) with initial improvement in symptoms reported a return or worsening of symptoms requiring a change in medication ( n  = 4, 12.1%) or left ventricular septal myomectomy ( n  = 7, 21.2%) during follow up. Conclusion: Disopyramide is a safe and effective treatment for LVOTO-related symptoms in childhood obstructive HCM. Any delay in the need for invasive intervention, particularly during childhood, is of clear clinical benefit. Highlights: Disopyramide is safe and effective in symptomatic children with obstructive HCM. Early symptomatic improvement was reported in >80%. Longer-term tachyphylaxis was seen in 1/3, requiring additional treatment.